Als secretaris van de N.V. tot afschaf. van alc. dranken aan zijn bureau in de W. Barentzstraat, Utrecht
Als secretaris van de N.V. tot afschaf. van alc. dranken aan zijn bureau in de W. Barentzstraat, Utrecht.